Nuclear and Mitochondrial SSU rRNA Genes Reveal Hidden Diversity of Haptophrya Endosymbionts in Freshwater Planarians and Challenge Their Traditional Classification in Astomatia - Rataj, Matej; Zhang, Tengyue; Vd’ačný, Peter (Frontiers in Microbiology, 2022)
Like many other aquatic animals, freshwater planarians have also become partners of symbiotic ciliates from the class Oligohymenophorea. In the present study, we explored the hidden diversity and addressed the questionable systematic position of mouthless obligatory gut endosymbionts of freshwater planarians, using the nuclear and mitochondrial SSU rRNA genes. Although all isolated ciliates morphologically corresponded to a single species, molecular analyses suggested the existence of three genetically distinct entities: H. planariarum, H. dugesiarum nov. spec., and H. schmidtearum nov. spec. The two former species share the same planarian host, which indicates a speciation model involving one duplication event without host switching. Such a diversification pattern was recognized also in astome ciliates inhabiting megascolecid and glossoscolecid earthworms. The present multi-gene phylogenies along with the secondary structure of the mitochondrial 16S rRNA molecule, however, challenge the traditional classification of Haptophrya within the subclass Astomatia. Haptophrya very likely evolved from an orphan scuticociliate lineage by the loss of oral apparatus and by the transformation of the thigmotactic field into an adhesive sucker. Since astomy evolved multiple times independently within the Oligohymenophorea, the loss of cell mouth cannot be used as a sole argument for the assignment of Haptophrya to the Astomatia anymore.